Penguatan Kewirausahaan melalui Pengenalan Business Model Canvas - Leonnard Ong (Journal of Sustainable Community Development (JSCD), 2023)
Business models simplify complex business realities into basic elements that are easy to create. The Business Model Canvas (BMC) has been popularized as a tool to help entrepreneurs describe, design, challenge, discover, and spin business models. BMC consists of nine basic building blocks that are used to describe the business model canvas, namely customer segments channels, key resources, key activities, value proposition, revenue stream, costs structure, customer relationship, and key partnership. BMC is often used in entrepreneurship training. In addition, many start-ups in Indonesia that are initiated by students require an effective way to turn ideas into businesses, namely a business model. In this community service study, it is hoped that it can provide more knowledge and practical skills in the business model canvas, as well as develop entrepreneurial potential for students. In the future, a more comprehensive survey research is needed to empirically evaluate the relationship between understanding BMC and increasing entrepreneurial potential for students.